“The Garifuna Teachers” of Belize: Legacy and Appropriations of a Historical Colonial Category in Nation-building Context - Ramírez Romero, Aïda (2023)
This paper reflects, from the case of the Garifuna Teachers in Belize, on the legacy and appropriation of identification categories, constructed during colonial times and rearticulated in a national context. Seeing identity as a social construction, discursive and situated, the paper analyzes firstly, specific case studies, how ethno-racial categories were discursively constructed and reproduced in colonial education context, and then, how they are appropriated by contemporaneous actors who crystalize the identity of the Garifuna group. The text is produced from historical literature on Belize and education, colonial archives produced in Belize at the beginning of the 20th century, collected in London (Kew), and interviews conducted in Belize, during 2017 and 2021. The article shows that differences continue to be constructed, in diverse ways, through ethno-racial distinctions in order to integrate the Garifuna identity in representations of Belize as a multicultural nation.